The Role of Institusional Ownership in Moderating the Effect of Executive Character, Transfer Pricing, and Sales Growth on Tax Avoidance - Nurul Qomaria; Hidayati Nasrah; Ari Nur Wahidah (JUEB : Jurnal Ekonomi dan Bisnis, 2026)
This study aims to examine the relationship between tax avoidance and executive character, transfer pricing, and sales growth for construction enterprises listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024, with institutional ownership serving as a moderating variable. Using purposive sampling, resulting in the selection of 11 construction companies that met the study criteria during the 2022–2024 period, for a total of 33 observations. Data handling and analysis using a moderated regression technique was carried out using Eviews 12. The results of the study reveal that executive characteristics have a significant negative effect on tax avoidance (Sig. = 0.004 < 0.05). Transfer pricing has no effect on tax avoidance (Sig. = 0.9687 > 0.05), while sales growth also has no effect on tax avoidance (Sig. = 0.1327 > 0.05). Institutional ownership moderates the effect of executive characteristics on tax avoidance (0.0270 < 0.05), but does not moderate the effects of transfer pricing (Sig = 0.9302 > 0.05) or sales growth (Sig = 0.2041 > 0.05) on tax avoidance. Tax avoidance is explained by the independent variables to the tune of 69.44%; the remaining variance is attributable to factors beyond the scope of this study.